Seven African countries show how the battle against malnutrition can be won - Hendriks, Sheryl L.; Glatzel, Katrin; Badiane, Ousmane (2017)
A number of African countries are taking bold action to tackle malnutrition. They have successfully implemented a range of actions that have started to improve nutrition for all.